Modular product design and customization - Pandremenos, J.; Chryssolouris, G. (Cranfield University Press, 2009)
The paper deals with modular design architecture and its capabilities for easy and fast customization in products. The basic principles of modularity are mentioned and the most known methodologies and tools for modular product design are reported. The way modularity can facilitate a product’s customization is being addressed. With the help of a modular real test case, a motorcycle helmet, the capabilities of modularity in customization are illustrated and a customization procedure is described. The conclusions drawn in the final section of the paper indicate that although many modular design methods exist none of them is capable to provide the optimum design solution. However, all of these methods undeniably facilitate the customization of products.
Organised by: Cranfield University
Keywords: Modularity; customization; design